Low-residue washing flux paste and preparation method thereof
By introducing nickel -copper microspheres and modified hydrogenation of hypoxida and modified hydrogenation in welded balm, the traditional lack of mechanical performance of the traditional welding balm welding joints, poor resistance to creep, poor storage stability, and insufficient thermal stability of the storage stability The problem realizes higher welding quality and electronic equipment reliability.
Patent Information
- Application Number
- CN202411807472.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-12-10
AI Technical Summary
The existing solder paste has insufficient mechanical properties after welding, poor creep resistance, poor storage stability, insufficient thermal stability, resulting in unstable welding quality and low reliability of electronic equipment.
Use low-residue water-washable solder paste, whose ingredients include flux, solder powder and nickel-copper microspheres loaded with cerium oxide. Modified hydrogenated rosin and modified titanium dioxide particles are used in the flux. The atomic molar ratio of nickel-copper microspheres is 3-4:2:1, and the average particle size is 200-300nm.
It improves the tensile strength, shear strength and thermal stability of the solder joints, enhances the shear resistance after soldering, improves the wettability and spreadability during the soldering process, and extends the storage stability of the solder paste.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of welding, and in particular to a low-residue water-washable soldering paste and a preparation method thereof. Background Art
[0002] In the modern electronic manufacturing industry, electronic welding is a key process for building electronic circuit connections. As electronic products continue to develop towards miniaturization, multifunctionality and high performance, the packaging density of electronic components is increasing, and the pin spacing is getting smaller and smaller, which puts higher requirements on welding quality and reliability. As a key auxiliary material in the welding process, the main function of flux paste is to remove oxides on the welding surface, prevent the metal surface from being oxidized again, reduce the surface tension of the solder, and promote the wetting and spreading of the solder on the welding part, thereby ensuring good welding quality, forming reliable electrical and mechanical connections, and ensuring the normal operation of electronic equipment.
[0003] Traditional soldering paste has many technical problems.
[0004] Insufficient solder joint strength: The mechanical properties of solder joints formed by traditional flux paste after welding may not meet the strict requirements of modern electronic products. For example, in some portable electronic devices, such as smart phones and tablets, they are often subjected to external forces such as falling and vibration. Solder joints welded with traditional flux paste may crack, desolder, etc. under the action of these external forces, causing electronic equipment failure. This is because traditional flux paste may not be able to effectively promote the full fusion of solder and welding surface during the welding process, and the internal structure of the formed solder joint is not dense enough, and there are defects such as pores, thereby reducing the mechanical performance indicators of the solder joint such as tensile strength and shear strength.
[0005] Poor creep resistance: During long-term use, electronic devices will be in different temperature environments, and solder joints will be affected by temperature stress. When the temperature changes in traditional soldering solder paste, creep may occur, that is, the solder joint slowly undergoes plastic deformation under long-term constant stress. This will cause the shape and size of the solder joint to change, which in turn affects the stability of the electrical connection, increases the circuit resistance, and even causes problems such as circuit breakage.
[0006] Storage stability issues: Traditional soldering paste is prone to stratification and drying up during storage. The soldering paste is usually a paste-like mixture of solder powder and flux. Due to the differences in physical properties such as density and particle size of different components, stratification is prone to occur during long-term storage. For example, some solid components (such as solder powder) in the soldering paste may settle to the bottom, while liquid components (such as solvents in the flux) will float on the upper layer, which will cause the composition of the soldering paste to be uneven and affect its performance. In addition, some volatile components in the flux may gradually evaporate during storage, causing the soldering paste to dry up and lose its original soldering performance.
[0007] Insufficient thermal stability: During the welding process, the solder joints will experience high temperatures. Conventional soldering pastes may undergo decomposition, oxidation and other reactions at high temperatures, producing harmful gases or forming unstable compounds. These reactions not only affect the air quality of the welding environment and harm the health of operators, but may also cause defects such as pores and inclusions in the solder joints, reducing the quality and reliability of the solder joints. Moreover, during the use of electronic products, the solder joints may also be subject to a certain degree of temperature fluctuations. The solder joints welded with conventional solder pastes may not be able to maintain stable performance under such temperature fluctuations, thus affecting the long-term stability of electronic equipment.
[0008] In summary, the soldering paste in the prior art has poor solderability and spreadability, and low shear resistance after welding. Summary of the invention
[0009] The invention provides a low-residue water-washable soldering paste and a preparation method thereof, so as to solve the problems of poor solderability and spreadability of the soldering paste in the prior art and low shear resistance after welding.
[0010] In order to achieve the above-mentioned invention object, the technical solution provided by the present invention is as follows:
[0011] A low-residue water-washable solder paste comprises a soldering flux, solder powder and nickel-copper microspheres loaded with cerium oxide. The raw materials of the soldering flux comprise modified hydrogenated rosin, a solvent, modified titanium dioxide particles and a composite activator. The atomic molar ratio of nickel, copper and cerium in the nickel-copper microspheres loaded with cerium oxide is 3-4:2:1, and the average particle size of the nickel-copper microspheres loaded with cerium oxide is 200-300 nm.
[0012] Preferably, the mass ratio of the soldering flux, solder powder, and nickel-copper microspheres loaded with cerium oxide is 9-12:90:0.05-0.08.
[0013] Preferably, the raw materials of the soldering flux include, by mass, 25-30 parts of modified hydrogenated rosin, 50-60 parts of solvent, 1-1.4 parts of modified titanium dioxide particles, 4-7 parts of compound activator, 0.5-1 part of emulsifier, 0.5-1 part of anionic surfactant, 0.3-0.4 part of corrosion inhibitor and / or 1-1.5 parts of film-forming agent.
[0014] Among them, ethanol: glycerol: 1,2-propylene glycol: ethylene glycol butyl ether are mixed in a mass ratio of 2:4:3:1 to obtain a solvent; oxalic acid: citric acid: triethanolamine are mixed in a mass ratio of 1:1:2 to obtain a composite activator; the emulsifier is a commercially available OP-10 emulsifier, the anionic surfactant is a commercially available sodium dodecylbenzene sulfonate, the corrosion inhibitor is corrosion inhibitor BTA, and the film-forming agent is polyethylene glycol 2000.
[0015] Preferably, the solder powder is a Sn-Ag-Cu alloy powder with an average particle size of 20-30 microns.
[0016] Preferably, the modified hydrogenated rosin is one or more of hydrogenated rosin yttrium, hydrogenated rosin calcium, and hydrogenated rosin zinc.
[0017] Preferably, the modified titanium dioxide particles are aluminum oxide modified titanium dioxide particles.
[0018] A method for preparing the low-residue water-washable soldering flux paste of the present invention comprises the following steps:
[0019] S1, modified hydrogenated rosin, solvent, modified titanium dioxide particles, compound activator, emulsifier, anionic surfactant, corrosion inhibitor and / or film-forming agent are mixed to obtain soldering flux;
[0020] S2, dissolving copper sulfate and nickel sulfate in water to obtain a metal salt solution;
[0021] S3, adding polyvinyl pyrrolidone to the metal salt solution to obtain a pre-reaction solution;
[0022] S4, adjusting the pH value of the pre-reaction solution, adding hydrazine hydrate, and performing a reduction reaction at 70-75° C., wherein the molar amount of the hydrazine hydrate is 3-4 times the total molar amount of the copper sulfate and the nickel sulfate, and foam will be generated during the reduction reaction, and the reaction is terminated when the foam subsides;
[0023] S5, after the reduction reaction is completed, a black precipitate is obtained, and the black precipitate is dried to obtain nickel-copper microspheres;
[0024] S6, placing the nickel-copper microspheres into a cerium nitrate alcohol solution to obtain a microsphere reaction solution, and ultrasonically immersing the microspheres at an ultrasonic power of 500-600 W for 1-2 h;
[0025] S7, taking out the microspheres in the impregnation solution, drying them at 90-120° C. for 6 h to obtain nickel-copper microspheres loaded with cerium oxide;
[0026] S8, mixing the soldering flux, solder powder and nickel-copper microspheres loaded with cerium oxide to obtain the soldering flux paste.
[0027] Preferably, the solute mass concentration of the metal salt solution in S2 is 20-30%.
[0028] Preferably, the mass of the polyvinyl pyrrolidone in S3 is 10-12% of the total mass of copper sulfate and nickel sulfate.
[0029] Preferably, the concentration of the cerium nitrate alcohol solution in S6 is 1-1.5 g / mL.
[0030] Preferably, since cerium oxide is adsorbed and loaded, it does not produce the effect that all cerium is loaded on the microspheres. Therefore, in actual preparation, according to the load ratio, the mass ratio of nickel copper microspheres to cerium nitrate alcohol solution needs to be selected to be 1:5-10.
[0031] The use of modified hydrogenated rosin (hydrogenated rosin yttrium, hydrogenated rosin calcium, hydrogenated rosin zinc, etc.) in the flux of the present invention can improve the thermal stability of the solder paste. Modified hydrogenated rosin is added with elements such as yttrium (Y), calcium (Ca), zinc (Zn), etc., which have excellent oxidation resistance and thermal stability. They can form stable chemical bonds with rosin molecules, further enhancing the antioxidant properties of hydrogenated rosin. Modified hydrogenated rosin can form a stable protective layer at the interface between the solder and the substrate, effectively preventing oxidation reactions in a high temperature environment and reducing oxidation of the solder and the substrate. The elements such as yttrium, calcium, and zinc in the modified hydrogenated rosin have high thermal conductivity, can effectively conduct heat during the welding process, reduce thermal stress, and improve the thermal stability of the welded joint. The modified hydrogenated rosin can be evenly distributed in the solder, so that heat can be quickly and evenly transferred to the welding area, reducing local overheating and thermal stress concentration, thereby improving the overall thermal stability. Modified hydrogenated rosin has good wettability and can better cover the surface of solder and substrate, promoting uniform bonding between solder and substrate. This uniform bonding helps reduce interface defects such as pores and cracks during welding, thereby improving the overall thermal stability of the welded joint. Modified hydrogenated rosin can effectively diffuse at the interface between solder and substrate, forming a uniform protective layer, reducing interface oxidation and corrosion, improving the thermal stability of the welded joint, and effectively preventing the decomposition of rosin molecules at high temperatures, maintaining the stability and functionality of the flux.
[0032] At the same time, the shear resistance of the weld layer after welding can be enhanced by adding modified titanium dioxide (particle size of 20nm). The modified titanium dioxide particles exist in the weld and interface as second phase particles, which can produce significant second phase strengthening effect. During the welding process, part of the TiO welding particles will dissolve in the Sn-rich phase, part of the TiO particles will settle on the surface of the Ag3Sn phase, and part of the TiO particles will settle on the surface of the Cu6Sn5 phase. After doping with modified titanium dioxide, the thickness of the IMC layer at the weld interface and the size of the IMC grains are reduced, achieving grain refinement and enhancing the hardness of the product.
[0033] In addition, the present invention introduces nickel-copper microspheres loaded with cerium oxide. First, cerium oxide can reduce the surface tension of the solder, making it easier for the solder to spread and wet on the welding surface, reducing poor wetting and cold soldering during the welding process. For example, when welding the pins of electronic components and the pads of the circuit board, it can ensure that the solder is evenly covered on the welding part to form a good welding joint. The nickel-copper microspheres themselves can be used as a good heat transfer medium, which can quickly transfer heat during the welding process, so that the solder reaches a molten state faster and is evenly distributed, further promoting the spreading and wetting of the solder, and improving the welding quality and efficiency.
[0034] Secondly, cerium oxide has a certain activity and may react slightly with the welding surface at high welding temperatures (such as interfacial reaction with metals such as copper and tin), forming a more stable chemical bond and enhancing the bonding force between the solder joint and the substrate. At the same time, nickel-copper microspheres can play a role similar to a reinforcing phase during the solidification process of the solder, forming a good metallurgical bond with the solder, preventing the expansion of cracks, and improving the tensile strength, shear strength and other mechanical properties of the solder joint. For example, when subjected to external forces (such as vibration and impact), the solder joint is less likely to crack or desolder, which improves the reliability and durability of the welded structure.
[0035] Finally, cerium oxide is an effective antioxidant. The cerium ions in its crystal structure can capture and neutralize the oxygen free radicals generated during the welding process to a certain extent, preventing further oxidation of the welded metal surface. The nickel-copper microspheres loaded with cerium oxide may react chemically with the original oxides on the welding surface during the welding process, reducing or converting the oxides into more volatile or soluble substances, thereby effectively removing the oxides on the welding surface and enabling the solder to better bond with the metal matrix. For example, for some easily oxidized metal surfaces (such as copper oxide that is easily formed on the copper surface), it can play a role in cleaning the surface and improve the weldability of the weld.
[0036] Compared with the prior art, the present invention has at least the following beneficial effects:
[0037] Modified hydrogenated rosin (hydrogenated rosin yttrium, hydrogenated rosin calcium, hydrogenated rosin zinc, etc.) is used in the present invention.
[0038] , can form a stable protective layer at the interface of solder and substrate, effectively prevent oxidation reaction in high temperature environment, reduce interface oxidation and corrosion, and improve thermal stability of welding joint; at the same time, modified titanium dioxide is added to enhance the shear resistance of welding layer after welding, realize grain refinement, and enhance the hardness of products; introduce nickel-copper microspheres loaded with cerium oxide, so that solder can be spread and wetted on welding surface more easily, prevent crack expansion, and improve mechanical properties such as tensile strength and shear strength of welding point. At the same time, the present invention also provides a preparation method of solder paste, which is simple to operate and has strong operability. DETAILED DESCRIPTION
[0039] In order to make the purpose, technical solution and advantages of the embodiment of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described below. Obviously, the described embodiment is a part of the embodiment of the present invention, not all of the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] The modified titanium dioxide particles involved in the following specific embodiments can be prepared by referring to the preparation method in Example 1 of the invention patent CN1454939A.
[0041] Yttrium hydrogenated rosin, calcium hydrogenated rosin, and zinc hydrogenated rosin can be prepared in the laboratory.
[0042] Preparation of yttrium hydrogenated rosin; Weigh 3.00g of propylene pimaric acid (purchased from Guangxi Wuzhou Richeng Forest Products Chemical Co., Ltd.), dissolve it in 30mL of anhydrous ethanol, and then add 70mL of distilled water to obtain a clear and transparent hydrogenated rosin solution. Weigh 1.11g of yttrium acetate (purchased from West Asia Reagent Company), dissolve it in 30mL of anhydrous ethanol by ultrasonication to obtain a milky white solution, and then add 70mL of distilled water to obtain a clear and transparent yttrium acetate solution. Then add the yttrium acetate solution dropwise to the hydrogenated rosin solution, start mechanical stirring while adding, react for 1.5h, generate a white precipitate, filter it, and wash it with anhydrous ethanol and deionized water (volume ratio of 20:6). Put it in a vacuum drying oven at 70℃ and vacuum dry it for 6h to obtain yttrium hydrogenated rosin.
[0043] Preparation of hydrogenated rosin calcium: weigh 20.00 g of hydrogenated rosin (purchased from Guangxi Wuzhou Richeng Forestry Chemical Co., Ltd.), dissolve it in 250 mL of anhydrous ethanol, weigh 3.68 g of KOH, and dissolve it in 30 mL of distilled water.
[0044] Dissolve, prepare KOH solution, add KOH aqueous solution dropwise to hydrogenated rosin ethanol solution, at this time the solution becomes turbid and then add 50mL distilled water, the solution is a yellow transparent liquid, after the KOH solution is added dropwise, the solution pH is about 9. Weigh 3.65g CaCl2, dissolve it with 100mL anhydrous ethanol by ultrasonic, and then add 32mL distilled water to obtain a clear and transparent calcium chloride solution. Then add the calcium chloride solution dropwise to the hydrogenated rosin potassium salt solution, start mechanical stirring while adding, the reaction generates a white precipitate, react for 2h, filter, wash with anhydrous alcohol and deionized water (volume ratio of 20:7), detect the washing end point with silver nitrate solution, and obtain a white solid. Put the product into a vacuum drying oven at 70℃ and vacuum dry for 6h to obtain hydrogenated rosin calcium.
[0045] Preparation of hydrogenated rosin zinc: Weigh 4.00 g of hydrogenated rosin, dissolve it in 100 mL of anhydrous ethanol, weigh 0.74 g of KOH, dissolve it in 20 mL of distilled water, prepare a KOH aqueous solution, add the KOH aqueous solution dropwise to the hydrogenated rosin ethanol solution, the solution becomes turbid, add 30 mL of distilled water, the solution is a light yellow transparent liquid, after the KOH aqueous solution is added dropwise, the pH of the solution is about 9. Weigh 0.90 g of ZnC12, dissolve it in 100 mL of anhydrous ethanol by ultrasonication, and then add 33 mL of distilled water to obtain a clear and transparent zinc chloride solution. Then add the zinc chloride solution dropwise to the hydrogenated rosin potassium salt solution, start mechanical stirring while adding, the reaction generates a white precipitate, react for 2 hours, filter, wash with anhydrous alcohol and deionized water (volume ratio of 3:1), detect the washing end point with silver nitrate solution, and obtain a white solid. Put the product into a vacuum drying oven at 70°C and vacuum dry for 6 hours to obtain hydrogenated rosin zinc.
[0046] The Sn-Ag-Cu alloy powder used in the specific implementation manner is YT-688 Sn-3.0wt.% Ag-0.5w.%Cu alloy powder produced by Yoshida Corporation of Japan.
[0047] Example 1
[0048] A low-residue water-washable solder paste is prepared by mixing solder flux, solder powder and nickel-copper microspheres loaded with cerium oxide in a mass ratio of 9:90:0.05.
[0049] The atomic molar ratio of nickel, copper and cerium in the nickel-copper microspheres loaded with cerium oxide is 3:2:1, and the average particle size of the nickel-copper microspheres loaded with cerium oxide is 200 nm.
[0050] The raw materials of the soldering flux include, by mass, 25 parts of hydrogenated rosin yttrium, 50 parts of solvent, 1 part of modified titanium dioxide particles, 4 parts of compound activator, 0.5 parts of emulsifier, 0.5 parts of anionic surfactant, 0.3 parts of corrosion inhibitor and 1 part of film former.
[0051] Among them, ethanol: glycerol: 1,2-propylene glycol: ethylene glycol butyl ether are mixed in a mass ratio of 2:4:3:1 to obtain a solvent; oxalic acid: citric acid: triethanolamine are mixed in a mass ratio of 1:1:2 to obtain a composite activator; the emulsifier is a commercially available OP-10 emulsifier, the anionic surfactant is a commercially available sodium dodecylbenzene sulfonate, the corrosion inhibitor is corrosion inhibitor BTA, and the film-forming agent is polyethylene glycol 2000.
[0052] The solder powder is a Sn-Ag-Cu alloy powder with an average particle size of 20 microns.
[0053] The modified titanium dioxide particles are aluminum oxide modified titanium dioxide particles.
[0054] A method for preparing the low-residue water-washable soldering flux paste of the present invention comprises the following steps:
[0055] S1, hydrogenated rosin yttrium, solvent, modified titanium dioxide particles, compound activator, emulsifier, anionic surfactant, corrosion inhibitor and film-forming agent are mixed to obtain soldering flux;
[0056] S2, adding copper sulfate and nickel sulfate into water at a molar ratio of 3:2 to obtain a metal salt solution with a solute mass concentration of 20%;
[0057] S3, adding polyvinyl pyrrolidone to the metal salt solution to obtain a pre-reaction solution, wherein the mass of polyvinyl pyrrolidone is 10% of the total mass of copper sulfate and nickel sulfate;
[0058] S4, adjusting the pH value of the pre-reaction solution to 10, adding hydrazine hydrate, and performing a reduction reaction at 70° C. for about 4 hours, wherein the molar amount of the hydrazine hydrate is 3 times the total molar amount of the copper sulfate and the nickel sulfate;
[0059] S5, after the reduction reaction is completed, a black precipitate is obtained, and the black precipitate is dried to obtain nickel-copper microspheres;
[0060] S6, placing the nickel-copper microspheres in a cerium nitrate alcohol solution with a concentration of 1 g / mL to obtain a microsphere reaction solution, wherein the mass ratio of the nickel-copper microspheres to the cerium nitrate alcohol solution is 1:5, and ultrasonic immersion is performed with an ultrasonic power of 500 W for 1 h;
[0061] S7, taking out the microspheres in the impregnation solution, drying at 90°C for 6h to obtain nickel-copper microspheres loaded with cerium oxide, and testing the elemental composition, the atomic molar ratio of nickel, copper and cerium is 3:2:1;
[0062] S8, mixing the soldering flux, solder powder and nickel-copper microspheres loaded with cerium oxide to obtain the soldering flux paste.
[0063] Example 2
[0064] A low-residue water-washable solder paste is prepared by mixing a solder flux, solder powder, and nickel-copper microspheres loaded with cerium oxide in a mass ratio of 12:90:0.08. The atomic molar ratio of nickel, copper, and cerium in the nickel-copper microspheres loaded with cerium oxide is 4:2:1, and the average particle size of the nickel-copper microspheres loaded with cerium oxide is 300 nm. The raw materials of the solder flux include 30 parts of hydrogenated rosin calcium, 60 parts of solvent, 1.4 parts of modified titanium dioxide particles, 7 parts of a composite activator, 1 part of an emulsifier, 1 part of an anionic surfactant, 0.4 parts of a corrosion inhibitor, and 1.5 parts of a film-forming agent in parts by mass. Among them, ethanol: glycerol: 1,2-propylene glycol: ethylene glycol butyl ether are mixed in a mass ratio of 2:4:3:1 to obtain a solvent; oxalic acid: citric acid: triethanolamine are mixed in a mass ratio of 1:1:2 to obtain a composite activator; the emulsifier is a commercially available OP-10 emulsifier, the anionic surfactant is a commercially available sodium dodecylbenzene sulfonate, the corrosion inhibitor is a corrosion inhibitor BTA, and the film-forming agent is polyethylene glycol 2000. The solder powder is a Sn-Ag-Cu alloy powder with an average particle size of 30 microns.
[0065] The modified titanium dioxide particles are aluminum oxide modified titanium dioxide particles.
[0066] A method for preparing the low-residue water-washable soldering flux paste of the present invention comprises the following steps:
[0067] S1, hydrogenated rosin calcium, solvent, modified titanium dioxide particles, compound activator, emulsifier, anionic surfactant, corrosion inhibitor and / or film-forming agent are mixed to obtain soldering flux;
[0068] S2, adding copper sulfate and nickel sulfate into water at a molar ratio of 4:2 to obtain a metal salt solution with a solute mass concentration of 30%;
[0069] S3, adding polyvinyl pyrrolidone to the metal salt solution to obtain a pre-reaction solution, wherein the mass of polyvinyl pyrrolidone is 12% of the total mass of copper sulfate and nickel sulfate;
[0070] S4, adjusting the pH value of the pre-reaction solution to 10, adding hydrazine hydrate, and performing a reduction reaction at 75° C. for about 4 hours, wherein the molar amount of the hydrazine hydrate is 4 times the total molar amount of the copper sulfate and the nickel sulfate;
[0071] S5, after the reduction reaction is completed, a black precipitate is obtained, and the black precipitate is dried to obtain nickel-copper microspheres;
[0072] S6, placing the nickel-copper microspheres in a cerium nitrate alcohol solution with a concentration of 1.5 g / mL to obtain a microsphere reaction solution, wherein the mass ratio of the nickel-copper microspheres to the cerium nitrate alcohol solution is 1:10, and ultrasonic immersion is performed with an ultrasonic power of 600 W for 2 h;
[0073] S7, taking out the microspheres from the impregnation solution, drying them at 120°C for 6 hours to obtain nickel-copper microspheres loaded with cerium oxide, and testing the elemental composition, the atomic molar ratio of nickel, copper and cerium is 4:2:1;
[0074] S8, mixing the soldering flux, solder powder and nickel-copper microspheres loaded with cerium oxide to obtain the soldering flux paste.
[0075] Example 3
[0076] A low-residue water-washable solder paste is prepared by mixing a solder flux, solder powder, and nickel-copper microspheres loaded with cerium oxide in a mass ratio of 10:90:0.06. The atomic molar ratio of nickel, copper, and cerium in the nickel-copper microspheres loaded with cerium oxide is 3.5:2:1, and the average particle size of the nickel-copper microspheres loaded with cerium oxide is 250nm. The raw materials of the solder flux include 27 parts of hydrogenated rosin zinc, 55 parts of solvent, 1.3 parts of modified titanium dioxide particles, 6 parts of a composite activator, 0.8 parts of an emulsifier, 0.7 parts of anionic surfactant, 0.35 parts of a corrosion inhibitor, and / or 1.3 parts of a film-forming agent in parts by mass. Among them, ethanol: glycerol: 1,2-propylene glycol: ethylene glycol butyl ether are mixed in a mass ratio of 2:4:3:1 to obtain a solvent; oxalic acid: citric acid: triethanolamine are mixed in a mass ratio of 1:1:2 to obtain a composite activator; the emulsifier is a commercially available OP-10 emulsifier, the anionic surfactant is a commercially available sodium dodecylbenzene sulfonate, the corrosion inhibitor is a corrosion inhibitor BTA, and the film-forming agent is polyethylene glycol 2000. The solder powder is a Sn-Ag-Cu alloy powder with an average particle size of 25 microns.
[0077] The modified titanium dioxide particles are aluminum oxide modified titanium dioxide particles.
[0078] A method for preparing the low-residue water-washable soldering flux paste of the present invention comprises the following steps:
[0079] S1, hydrogenated rosin zinc, solvent, modified titanium dioxide particles, compound activator, emulsifier, anionic surfactant, corrosion inhibitor and / or film-forming agent are mixed to obtain soldering flux;
[0080] S2, adding copper sulfate and nickel sulfate into water at a molar ratio of 3.5:2 to obtain a metal salt solution with a solute mass concentration of 27%;
[0081] S3, adding polyvinyl pyrrolidone to the metal salt solution to obtain a pre-reaction solution, wherein the mass of polyvinyl pyrrolidone is 11% of the total mass of copper sulfate and nickel sulfate;
[0082] S4, adjusting the pH value of the pre-reaction solution to 10, adding hydrazine hydrate, and performing a reduction reaction at 73° C. for about 4 hours, wherein the molar amount of the hydrazine hydrate is 3.5 times the total molar amount of the copper sulfate and the nickel sulfate;
[0083] S5, after the reduction reaction is completed, a black precipitate is obtained, and the black precipitate is dried to obtain nickel-copper microspheres;
[0084] S6, placing nickel-copper microspheres in a 1.2 g / mL cerium nitrate alcohol solution to obtain a microsphere reaction solution, wherein the mass ratio of the nickel-copper microspheres to the cerium nitrate alcohol solution is 1:8, and ultrasonic immersion is performed at an ultrasonic power of 550 W for 1.5 h;
[0085] S7, taking out the microspheres from the impregnation solution, drying at 110° C. for 6 h to obtain nickel-copper microspheres loaded with cerium oxide, and testing the elemental composition, the atomic molar ratio of nickel, copper and cerium is 3.5:2:1;
[0086] S8, mixing the soldering flux, solder powder and nickel-copper microspheres loaded with cerium oxide to obtain the soldering flux paste.
[0087] Comparative Example 1
[0088] This comparative example is the same as Example 1, except that in this comparative example, an equal amount of nickel-copper microspheres loaded with cerium oxide are replaced by solder powder.
[0089] Comparative Example 2
[0090] This comparative example is the same as Example 1, except that there is no step S6-7 in this comparative example, and the nickel-copper microspheres loaded with cerium oxide are replaced by the nickel-copper microspheres in S5.
[0091] Comparative Example 3
[0092] This comparative example is the same as Example 1, except that in this comparative example, the modified titanium dioxide particles are replaced with an equal amount of a film-forming agent.
[0093] Comparative Example 4
[0094] This comparative example is the same as Example 1, except that in this comparative example, the mass ratio of the flux, the solder powder, and the nickel-copper microspheres loaded with cerium oxide is 9:90:0.03.
[0095] Comparative Example 5
[0096] This comparative example is the same as Example 1, except that in this comparative example, the mass ratio of the flux, the solder powder, and the nickel-copper microspheres loaded with cerium oxide is 9:90:0.1.
[0097] Comparative Example 6
[0098] This comparative example is the same as Example 1, except that there is no step S6-7 in this comparative example, and the nickel-copper microspheres loaded with cerium oxide are replaced by the cerium oxide microspheres in S5 in equal amounts.
[0099] The solder pastes in Examples 1-3 and Comparative Examples 1-6 were subjected to performance tests, and the main test contents were: solderability test, spreadability test and maximum shear resistance test. Among them, solderability is an indicator used to evaluate the soldering activity of solder paste. The solderability test was conducted using a SAT5100 solderability tester, and the main test method was: setting the instrument measurement parameters, setting the solder tank heating temperature to (260 ± 5) 6, the Cu sheet immersion depth to 5mm, and the immersion time to 10s; placing the solder paste sample in the solder tank and heating and melting it, and taking three standard Cu sheets to immerse the solder paste sample for testing; the wetting force curve was obtained through testing, and the wetting time, maximum wetting force and other related indicators were read and their average values were calculated. For solder paste, the smaller the wetting time, the greater the maximum wetting force, indicating that the wetting effect of the solder paste sample on the Cu sheet during welding is better, that is, the stronger the solderability.
[0100] The spreadability test refers to the IPC-TM-650 standard. The spreadability test is an important research method used to evaluate the soldering performance of solder paste. Test method: Use a template with a leak hole diameter of 6.5mm and a thickness of 0.2mm to print 3 solder paste patterns on a Cu substrate; put the Cu substrate printed with solder paste patterns into a T200N flow soldering furnace with a peak temperature of (260±5)6 to heat; after cooling, take out the sample, observe the spread morphology of the solder joint, measure its spread area, spread rate and wetting angle, and take the average value of the 3 solder joint samples.
[0101] The lap-shear shear model was used for the maximum shear resistance test. The base material size was 30x5x1mm copper bar. During the welding process, a steel mesh with an opening of 5*5*0.2mm was used to print the solder paste onto the surface of the copper sheet, which ensured that the amount of solder paste was consistent each time. Finally, the reflow furnace was adjusted to a maximum temperature of 260°C and maintained for 1 minute to complete the welding. The maximum shear resistance after welding was measured.
[0102] The solderability test results are shown in Table 1;
[0103] Table 1 Solderability test results
[0104] Group Maximum wetting force (mN) Final wetting force (mN) Zero crossing time(s) Wetting time(s) Example 1 4.31 4.23 1.01 1.32 Example 2 4.42 4.26 0.93 1.13 Example 3 4.26 4.12 1.12 1.21 Comparative Example 1 3.21 3.10 1.51 1.63 Comparative Example 2 4.11 3.92 1.21 1.28 Comparative Example 3 3.55 3.45 1.33 1.37 Comparative Example 4 4.13 4.1 1.19 1.22 Comparative Example 5 4.32 4.3 0.98 1.1 Comparative Example 6 3.98 3.87 1.26 1.31
[0105] The results of the spreadability test are shown in Table 2;
[0106] Table 2 Spreadability test results
[0107] Group Spreading area (mm) Spreading rate (%) Wetting angle Example 1 64.3 90.5 10.6 Example 2 65 91.1 9.8 Example 3 65.6 91.8 9.6 Comparative Example 1 53 84.8 13.2 Comparative Example 2 61.1 87.9 11.2 Comparative Example 3 58.3 86.5 12.4 Comparative Example 4 60.2 86.3 11.7 Comparative Example 5 66.1 91.4 9.7 Comparative Example 6 59.2 87.1 12.1
[0108] The shear resistance test results are shown in Table 3;
[0109] Table 3 Maximum shear resistance
[0110] Group Maximum shear resistance (MPa) Example 1 32.4 Example 2 33.6 Example 3 31.5 Comparative Example 1 26.8 Comparative Example 2 29.6 Comparative Example 3 27.4 Comparative Example 4 28.1 Comparative Example 5 27.2 Comparative Example 6 29.7
[0111] It can be seen from the test results in Tables 1-3 that the soldering paste of the present invention has good solderability and wettability, and high shear resistance after welding. When the amount of nickel-copper microspheres loaded with cerium oxide is too low, the wettability, spreadability and shear resistance after welding are reduced. When it is too high, although the wettability and spreadability are improved, the shear resistance is reduced. This may be because too much nickel-copper microspheres loaded with cerium oxide have an adverse effect on the shear resistance while improving the wettability.
[0112] The above are only specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. The protection scope of the present invention shall be based on the protection scope of the claims.
Claims
1. A low-residue water-washable soldering paste, characterized in that: The invention comprises a soldering flux, solder powder and nickel-copper microspheres loaded with cerium oxide. The raw materials of the soldering flux comprise modified hydrogenated rosin, a solvent, modified titanium dioxide particles and a compound activator. The atomic molar ratio of nickel, copper and cerium in the nickel-copper microspheres loaded with cerium oxide is 3-4:2:1, and the average particle size of the nickel-copper microspheres loaded with cerium oxide is 200-300nm.
2. The low-residue water-washable flux paste according to claim 1, characterized in that: The mass ratio of the soldering flux, solder powder and nickel-copper microspheres loaded with cerium oxide is 9-12:90:0.05-0.
08.
3. The low-residue water-washable soldering paste according to claim 1, characterized in that: The raw materials of the soldering flux include 25-30 parts of modified hydrogenated rosin, 50-60 parts of solvent, 1-1.4 parts of modified titanium dioxide particles, 4-7 parts of compound activator, 0.5-1 part of emulsifier, 0.5-1 part of anionic surfactant, 0.3-0.4 part of corrosion inhibitor and / or 1-1.5 parts of film former, by weight.
4. The low-residue water-washable soldering paste according to claim 1, characterized in that: The solder powder is Sn-Ag-Cu alloy powder with an average particle size of 20-30 microns.
5. The low-residue water-washable flux paste according to claim 1, characterized in that: The modified hydrogenated rosin is one or more of hydrogenated rosin yttrium, hydrogenated rosin calcium, and hydrogenated rosin zinc.
6. The low-residue water-washable flux paste according to claim 1, characterized in that: The modified titanium dioxide particles are aluminum oxide modified titanium dioxide particles.
7. A method for preparing a low-residue water-washable flux paste according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1, modified hydrogenated rosin, solvent, modified titanium dioxide particles, compound activator, emulsifier, anionic surfactant, corrosion inhibitor and / or film-forming agent are mixed to obtain soldering flux; S2, dissolving copper sulfate and nickel sulfate in water to obtain a metal salt solution; S3, adding polyvinyl pyrrolidone to the metal salt solution to obtain a pre-reaction solution; S4, adjusting the pH value of the pre-reaction solution, adding hydrazine hydrate, and performing a reduction reaction at 70-75° C., wherein the molar amount of the hydrazine hydrate is 3-4 times the total molar amount of the copper sulfate and the nickel sulfate; S5, after the reduction reaction is completed, a black precipitate is obtained, and the black precipitate is dried to obtain nickel-copper microspheres; S6, placing the nickel-copper microspheres into a cerium nitrate alcohol solution to obtain a microsphere reaction solution, and ultrasonically impregnating the solution; S7, taking out the microspheres in the impregnation solution, and drying them to obtain nickel-copper microspheres loaded with cerium oxide; S8, mixing the soldering flux, solder powder and nickel-copper microspheres loaded with cerium oxide to obtain the soldering flux paste.
8. The preparation method according to claim 7, characterized in that: The solute mass concentration of the metal salt solution in S2 is 20-30%.
9. The preparation method according to claim 7, characterized in that: The mass of the polyvinyl pyrrolidone in S3 is 10-12% of the total mass of copper sulfate and nickel sulfate.
10. The preparation method according to claim 7, characterized in that: The concentration of the cerium nitrate alcohol solution in S6 is 1-1.5 g / mL, and the mass ratio of the nickel-copper microspheres to the cerium nitrate alcohol solution is 1:5-10.
Citation Information
Patent Citations
Method of preparing nano titanium dioxide granule with surface coated of aluminium oxide
CN1454939A
Cerium dioxide nanoparticle reinforced tin silver copper composite soldering paste and preparation method thereof
CN108526747A
Alloy solder and preparation method thereof
CN118023761A
Metal soldering paste for martensitic stainless steel complex structure and preparation method
CN118559280A
Friction stir welding and processing of oxide dispersion strengthened (ODS) alloys
US20120070686A1